To explore the postoperative nutritional status and factors influencing prognosis in patients with chronic constipation complicated by malnutrition - Wang, Le; Tian, Hongliang; Li, Long; Ye, Chen; Cui, Jiaqu; Lin, Zhiliang; Yang, Bo; Zhao, Di; Li, Ning; Feng, Xiaobo; Chen, Qiyi (Frontiers in Medicine, 2024)
Background Many patients with constipation also suffer from varying degrees of malnutrition, and the relationship between the two conditions is a vicious cycle. Surgery is the final step in the treatment of constipation, with a success rate of up to 95%. This study aims to investigate the effects of surgical treatment on the nutritional status of patients with chronic constipation and malnutrition. Methods A total of 60 patients with chronic constipation and various degrees of malnutrition who underwent surgery in our department from January 2020 to March 2023 were included in this study. Biochemical tests including BMI, albumin, total protein, hemoglobin, cholesterol and lymphocyte count were conducted, as well as measurements of inflammatory markers such as Interleukin-6 (IL-6), Interleukin-8 (IL-8), and C-reactive protein (CRP). Additionally, multiple nutritional risk screening scales (NRS2002, MUST, NRI, and MNA) and the prognostic nutritional index (PNI) were used to assess the nutritional status of patients before surgery, as well as at 1 month, 3 months, and 6 months post-surgery. Finally, we analyzed the factors influencing postoperative recovery outcomes in patients. Results Compared to pre-operation, the BMI of patients significantly increased at 1 month, 3 months, and 6 months after the operation, with statistically significant differences (p < 0.001). Multiple nutritional risk assessment tools (NRS2002, MUST, NRI, and MNA), as well as the prognostic nutritional index (NPI), indicated a reduction in nutritional risk and improvement in nutritional status at 1, 3, and 6 months post-surgery, compared to pre-surgery levels (p < 0.001). The levels of albumin, total protein, and hemoglobin in patients at 1, 3, and 6 months after the surgery were significantly higher than those before the surgery (p < 0.001). However, there was no significant change in the number of lymphocytes. Inflammatory markers such as IL-6, IL-8, and CRP exhibited a significant decrease after the surgery, reaching normal levels at 6 months post-surgery (p < 0.001). Low BMI, low PNI, and low cholesterol levels are independent risk factors for patient prognosis (p < 0.05). Conclusion Surgical treatment can enhance the nutritional status of constipation patients with malnutrition, which in turn promotes the restoration of intestinal motility. The patient’s nutritional status will impact the postoperative recovery outcomes.